HSP90 inhibitors strengthen extracellular ATP‐stimulated synthesis of interleukin‐6 in osteoblasts: Amplification of p38 MAP kinase. (21st June 2020) - Hioki, Tomoyuki; Tokuda, Haruhiko; Nakashima, Daiki; Fujita, Kazuhiko; Kawabata, Tetsu; Sakai, Go; Kim, Woo; Tachi, Junko; Tanabe, Kumiko; Matsushima‐Nishiwaki, Rie; Otsuka, Takanobu; Iida, Hiroki; et al.
Abstract : Heat shock protein 90 (HSP90) is expressed ubiquitously in a variety of cell types including osteoblasts. HSP90 acts as a key driver of proteostasis under pathophysiological conditions. Here, we investigated the involvement of HSP90 in extracellular ATP‐stimulated interleukin (IL)‐6 synthesis and HSP90 downstream signalling in osteoblast‐like MC3T3‐E1 cells. In osteoblasts, extracellular ATP stimulates the synthesis of IL‐6, a bone‐remodelling agent. Geldanamycin, 17‐allylamino‐17‐demethoxy‐geldanamycin (17‐AAG) and onalespib, three different HSP90 inhibitors, amplified the ATP‐stimulated IL‐6 release. Geldanamycin increased IL‐6 mRNA expression elicited by ATP. ATP enhanced the triiodothyronine‐induced osteocalcin release, but HSP90 inhibitors suppressed the release. Extracellular ATP induced the phosphorylation of p44/p42 mitogen‐activated protein kinase (MAPK), p38 MAPK, c‐ Jun N‐terminal kinase (JNK), p70 S6 kinase, Akt, and myosin phosphatase‐targeting subunit (MYPT), a Rho‐kinase substrate. SB203580, an inhibitor of p38 MAPK, suppressed ATP‐stimulated IL‐6 release. Inhibitors of MEK1/2 (PD98059), JNK (SP600125), upstream kinase of p70 S6 kinase (rapamycin) and Akt (deguelin), all increased IL‐6 release. Y27632, a Rho‐kinase inhibitor, failed to affect the IL‐6 release stimulated by ATP. Geldanamycin and 17‐AAG both amplified ATP‐induced p38 MAPK phosphorylation, although geldanamycin inhibited the phosphorylation of Akt induced by ATP. In addition, SB203580 significantly reduced the amplification by geldanamycin of the IL‐6 release. Taken together, our results strongly suggest that HSP90 inhibitors up‐regulate extracellular ATP‐stimulated IL‐6 synthesis via amplification of p38 MAPK activation in osteoblasts. Significance of the study: Heat shock protein 90 (HSP90) acts as a key driver of proteostasis under pathophysiological conditions in a variety of cell types. We have previously shown that HSP90 is expressed at high levels in osteoblast‐like MC3T3‐E1 cells, even in their quiescent state, consistent with HSP90 performing an important physiological function in osteoblasts. In the present study, we investigated whether HSP90 is implicated in extracellular ATP‐induced interleukin (IL)‐6 synthesis in osteoblast‐like MC3T3‐E1 cells. Our results strongly suggest that HSP90 inhibitors up‐regulate extracellular ATP‐stimulated IL‐6 synthesis via amplification of p38 mitogen‐activated protein kinase activation in osteoblasts.